CHEMICAL LEASING AS A NEW BUSINESS MODEL CONTRIBUTING TO SUSTAINABLE INDUSTRIAL DEVELOPMENT - Peceva, Maja; Rizov, Tashko; Kochov, Atanas (Mechanical Engineering – Scientific Journal, 2016)
The intensive use of natural resources and the increased amount of waste that influence negatively on the water and air pollution, gives us the concern to think more globally about new approaches and methods of work that will lead us to constant development of the concepts ensuring sustainable development. For this purpose, UNIDO developed a new business model for chemical management that is focused on providing services instead of selling substances. The aim of the Chemical Leasing concept as a business model is not only to change the traditional trade of chemicals and give value to the service that the chemicals do, but also to develop partnership between producers and consumers of different chemicals globally. Chemical leasing reduces the consumption of chemicals and optimizes their usage. It provides environmental, safety and economy improvements for all parties included in the concept. It is a challenge for small and medium sized enterprises to improve their image by participating in this innovative venture in developing countries and economy in transition. This paper presents the fundamentals of the chemical leasing concept and analysis its contribution to the sustainable industrial development.
Keywords: chemical leasing; cleaner production; sustainable development